M-Wave and F-Wave Parameters in Relation to Recording Electrode Placement - Masataka Kurobe; Naoki Kado; Toshiaki Suzuki (Annals of Rehabilitation Medicine, 2026)
Objective: To clarify the influence of recording electrode placement on F-wave parameters, we investigated F-wave parameters recorded from the abductor pollicis brevis muscle using different recording electrode positions.Methods: Thirteen healthy volunteers participated. Recording electrodes were placed at four locations (20, 30, 40, and 50 mm from the reference electrode). The stimulating electrode was positioned over the median nerve at the wrist, and the reference electrode was placed on the distal tendon of the abductor pollicis brevis muscle. Stimulation intensity was set at 1.2 times that required to elicit the maximal M-wave amplitude. Thirty stimuli were delivered at 0.5 Hz. Outcome measures included M-wave latency and amplitude, F-wave mean latency and amplitude, F/M amplitude ratio, and F-wave persistence. Data were analyzed using one-way repeated-measures analysis of variance, and effect sizes were calculated using partial η².Results: M-wave amplitude varied substantially according to recording electrode position (partial η²=0.50). In contrast, effect sizes were small for most F-wave parameters. The F/M amplitude ratio did not reach statistical significance but demonstrated a moderate-to-large effect size (partial η²=0.24).Conclusion: Recording electrode placement substantially affected M-wave amplitude and may also influence the F/M amplitude ratio. Therefore, consistent electrode placement should be maintained when interpreting these parameters in clinical or research settings. However, given the relatively small sample size, clinically meaningful effects on other F-wave parameters cannot be excluded and should be investigated in larger studies.